Strategi Pengembangan Pariwisata Berdasarkan Daya Dukung Wisata Dan CHSE Pada Masa Pandemi Covid-19 - Hanun Nurrahma; Luchman Hakim; Rita Parmawati (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
The reopening of Red Island Beach since July 2020 still has several important problems that must be solved in order to overcome the spread of Covid-19 in tourism areas. The limitation of tourists has not been implemented properly by the tourist managers. It can be seen from the unrealistic decision of the tourist managers to still allow the visitors come even though it already passed the maximum of tourists that can visit during the pandemic. Meanwhile, based on the CHSE facilities, the result showed there are several things which still inappropriate and must be fixed. This research aim to examine the external and internal factors in the reopening of Red Island Beach and also form both of alternative and priority strategies which can be used for the future growth. The results of the data collected through interviews and questionnaires will be analyzed deeply using SWOT-AHP. After the SWOT analysis was found, it showed that the current position of Red Island Beach is in Quadrant VII, which means that the strategy suggested for the development of Red Island Beach is using the concentric diversification strategy. Meanwhile, the result of AHP analysis in all criteria and sub-cateria has a value CR < 0.1, it means the study is consistent and can be used for choosing the priority strategies in Red Island Beach. Those priority strategies are about increasing visitor managements and adding the supporting infrastructure that related with the value of the carrying capacity of Red Island Beach.